PENGARUH SUKU BUNGA TABUNGAN, TINGKAT INFLASI DAN INDEKS HARGA SAHAM GABUNGAN (IHSG) TERHADAP PENGHIMPUNAN TABUNGAN PADA BANKBANK UMUM DI KALIMANTAN BARAT - B01111067, SENEN (Jurnal Curvanomic, 2015)
The purpose of this research is to test the variables of interest rates, inflationand Composite Stock Price Index in influencing the accumulation of savings Commercial Bank has an important role in supporting the economy of societyin West Kalimantan. The development and performance of commercial banks inrunning their intermediation role is very supported by the amount of private savingsthat can be collected and then distributed in the form of credit. This research is using the method that seeks causal comparative study the cause or reason for interest rates, inflation and composite stock price index in orderto obtain an answer from the causes of fluctuations accumulation of savings made bycommercial banks, as well as the search for the causes that complete and accurateinformation on the influence of the three factors on saving in commercial banks. Bytesting OLS (Ordinary Least Square) methods using software Eviews 6. The results showed, interest rates, inflation and stock price indexsimultaneously affect the saving on Commercial Banks in West Kalimantan.However, partial, interest rates have a significant effect with a negative direction, theinflation rate has no real influence, for private savings in commercial banks in West Kalimantan, while the Composite Stock Price Index has positive influence on theaccumulation of saving in commercial banks in West Kalimantan.Keywords: Saving on Commercial Banks, Interest Rate, Inflation and Composite    Stock Price Index